FUNDAMENTAL ISSUES WITH ISSUES WITH REINCARNATION AS A BELIEF - Onwuatuegwu, Ignatius Nnaemeka (Journal of Philosophy, Culture and Religion, 2020)
Purpose: Although reincarnation seems much like a traditional African belief or thought, the paper attempts to look into the fundamental issues that surround the belief on reincarnation. The paper also tries not to limit the discussion on the fundamental issues of reincarnation as a belief that is just peculiar to Africa. The paper tends to make extensive coverage on the fundamental issues on reincarnation as abelief system beyond the shores of African culture. Methodology: Review of related literatures and peer review journals, as well as internet sources were applied in the discourse made in this paper. Findings: The concept of reincarnation, also known as rebirth is the belief that a person (after his or her death) can be born again, often in the same family or locality where he was initially born.and the paper also found that the issues of reincarnation seems to be gaining popularity in the Western world. Reincarnation is not just addressed as a primitive belief system that is overemphasized and needs to be overlooked. However, it is not out of place to state that the popular notion about the concept of reincarnation breeds certain illogical phenomena and makes it look so superstitious and seemingly difficult to understand, therefore, creating rationale to negate the realistic nature of the concept. Unique Contribution to Theory, Practice And Policy: There is no much literature on the analysis of the fundamental issues of reincarnation. It follows that there are dearth of adequate clarifications on the fundamental issues surrounding reincarnation as a belief; as such are not fully covered comprehensively in any single book. Therefore, this study tends to utilize this paper as a means to make further clarifications on the fundamental issues on reincarnation as a belief. This paper analyses what reincarnation means, what reincarnates in humans, is it the soul or the body, or both (or a nonphysical entity) that reincarnates, or nothing in reality? If a person constitutes the body and soul, then what is the co-relationship between the two? These are some of the questions that this paper will answer.